(3aVGFd GdbQBf hBOGHg heYGdegs - (3GHf SdGe GdLeMjj , eMeO Hf SdGe Hf YHjOGddg Hf SGde, CHh YHO Gddg GdLeMjj GdHUQj,J (B232 (3g` s
(3ChdgG (B:s
(3HGH aVd GdbQBf hJYedg hJYdjeg ddfGS s
(3BNQgG (B:s
(3MGaXhG Ydi GdUhGJ hGdUdGg GdhSWi hUdGI GdYUQ CTgO Cfi SeYJgG ef QShd Gddg Udi Gddg Ydjg hSde BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3Ydi GdfSNI ELGRGJ bOjeI JajO bQGAJgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B41s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1277s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs